RESEARCH OF IR SPECTROSCOPY INDICATORS OF THE AURIN COMPOUND, WHICH CONTAINS NITROGEN - Gulboeva, Dilafruz; Smanova, Zulayxo (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
It is known, that during the production of polyvinyl chloride in industry, chlororganics are release as a by-product. These additional decoupling chlororganics were isolated and sorbent agents were created from the amines produced by the processing. The sorbents obtained during the practical experiments of the study were establish to be use to treat industrial wastewater Cu (II) and Zn (II) ions. In the course of practical experiments, the functional groups in the sorbent obtained were analyzed IR spectroscopy indicators.